O ensino do número de Euler - Micolino, Andressa Luana (2024)
This study investigates Euler’s number, highlighting its relevance both in mathematics and in practical applications, such as financial mathematics and the study of natural phenomena. The main objective is to propose innovative teaching strategies to facilitate the understanding of this concept in Basic Education. The research includes a theoretical review of its historical development, an analysis of its treatment in textbooks and national exams, and the development of an educational resource in the form of a game based on progressive challenges. The results suggest that the use of interactive approaches enhances the comprehension of abstract mathematical concepts, aligning with the requirements of the National Common Curricular Base (BNCC) and the National High School Exam (ENEM).